2013
DOI: 10.1002/mnfr.201200803
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of milk on the absorption of dietary phenolic acids and the change in human plasma antioxidant capacity through a mechanism involving both milk proteins and fats

Abstract: Milk proteins and fats together, but not alone, are responsible for the inhibitory effect of milk on the absorption of phenolic acids and the change in plasma antioxidant capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The varying protein and fat contents within the commercial milk products (Table 1) did not impact the bioaccessibility of phenols, flavonoids or anthocyanins, and no significant difference (P > 0.05) was observed in TPC, TFC and TAC between the milk samples (Figure 5a-c). The combination of fat and protein in WM has been shown to reduce the phenolic bioavailability from a blend of jujube juice and milk (Zhang et al 2012(Zhang et al , 2013. This supports the findings of the current study, which showed a significant decrease (P ≤ 0.05) in phenolic bioaccessibility in milk in comparison with water.…”
Section: Bioaccessibility Of Phenolics Flavonoids and Anthocyaninssupporting
confidence: 90%
“…The varying protein and fat contents within the commercial milk products (Table 1) did not impact the bioaccessibility of phenols, flavonoids or anthocyanins, and no significant difference (P > 0.05) was observed in TPC, TFC and TAC between the milk samples (Figure 5a-c). The combination of fat and protein in WM has been shown to reduce the phenolic bioavailability from a blend of jujube juice and milk (Zhang et al 2012(Zhang et al , 2013. This supports the findings of the current study, which showed a significant decrease (P ≤ 0.05) in phenolic bioaccessibility in milk in comparison with water.…”
Section: Bioaccessibility Of Phenolics Flavonoids and Anthocyaninssupporting
confidence: 90%
“…In our recent study, after excluding the effects of other macronutrients, it was found that milk proteins led to significant changes in the plasma kinetics profile of polyphenols but did not affect the overall absorption of polyphenols in rats ( 9 ) . Similarly, it was also found that milk proteins extended the time needed to reach a maximal plasma polyphenol concentration in human subjects ( 10 ) . Casein, which is a major component of milk protein, can form curds in the stomach that delay casein's absorption compared with other proteins ( 165 ) .…”
Section: Interaction Of Plant Phenols With Food Macronutrients: In VImentioning
confidence: 91%
“…Recently, a novel effect of fat on the bioavailability and antioxidant activity of polyphenols was found. At a relatively low content (3·8 % (w/v) in milk), milk fat alone did not interact with polyphenols and did not have an effect on the bioavailability and antioxidant activity of polyphenols in rats and human subjects ( 9 , 10 ) . Similarly, milk proteins did not affect the absorption and antioxidant activity of polyphenols.…”
Section: Interaction Of Plant Phenols With Food Macronutrients: In VImentioning
confidence: 96%
See 2 more Smart Citations